Paving the Way Ahead: A Systematic Literature Analysis of Inclusive Teaching Practices in Inclusive Classrooms - Aarti Singh; Pratima Pallai (LED Edizioni Universitarie, 2023)
Classroom deliberations in an inclusive environment is challenging yet rewarding. Teaching students with varied needs under the same roof provides the teachers with the opportunity to bring out their best and to help students to attain an optimum level of learning. The purpose set for this paper is to conduct a rigorous review of inclusive teaching-learning practices across countries to understand and present the best ways of conducting an inclusive classroom. To explore the stated objective the researchers opted for an extensive desk review method to review the available related literature in a systematic manner. As a result of conducting a systematic review analysis, certain themes have emerged under which plausible inclusive practices have been presented as a finding of the research. The study presented five categories of best teaching practices that emerged from the review. This paper presented a concise and accumulated version of the best practices and methods adopted by the practitioners in inclusive education across the world. Amalgamated findings present that using ICT, individualised learning and various classroom management techniques, collaboration and curriculum adaptations provide the best ways to promote inclusion.